2019
DOI: 10.1016/j.hpb.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Five year experience of gallbladder polyp surveillance and cost effective analysis against new European consensus guidelines

Abstract: Background: Gallbladder polyp (GBP) surveillance seeks to identify early neoplasms, but practice varies amongst surgical units. Recent European consensus guidelines have recommended an evidencebased GBP surveillance strategy. In a tertiary centre Hepato-Pancreato-Biliary unit we examine GBP surveillance, malignant yield, and assess cost-effectiveness of the new European consensus guidelines.Methods: Respective data were collected from all patients with ultrasonography-detected GBPs between January 2008 and Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…16 Patel et al found that the management of gallbladder polyps based on the European consensus guidelines would be clinically cost-effective, but will significantly increase the proportion of patients requiring cholecystectomy. 15,20 Currently, no studies have been conducted to assess the impact of following these guidelines, larger-scale retrospective and prospective studies are needed to assess the benefit of managing gallbladder polyps in accordance with current guidelines.…”
Section: Gallbladder Polypsmentioning
confidence: 99%
“…16 Patel et al found that the management of gallbladder polyps based on the European consensus guidelines would be clinically cost-effective, but will significantly increase the proportion of patients requiring cholecystectomy. 15,20 Currently, no studies have been conducted to assess the impact of following these guidelines, larger-scale retrospective and prospective studies are needed to assess the benefit of managing gallbladder polyps in accordance with current guidelines.…”
Section: Gallbladder Polypsmentioning
confidence: 99%
“…However, polyp number, shape, patient age, and sessile features also have been demonstrated as the high-risk clinical factors in previous studies [7] [8]. In addition, a considerable part of patients who underwent cholecystectomy according to the guidelines proved to be non-neoplastic polyps, and these patients bared unnecessary surgical risks and economic burdens [9]. Moreover, incidental gallbladder carcinoma in cases with polyps less than 10mm were frequently reported [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A considerable number of patients who underwent cholecystectomy in accordance with GBP management guidelines were shown to have non-neoplastic polyps. 9 These patients experienced unnecessary surgical risks and economic burdens. Moreover, incidental GBC in cases with polyps <10 mm have been reported.…”
Section: Introductionmentioning
confidence: 99%